Surat al-tadayyun al-wasat: dirasah wasafiyyah - Khan, Israr Ahmad; Khan, Musaddiq Majid (International Islamic University Malaysia, 2014)
This study is concerned with the meaning of moderate religiosity based on the verses of the Holy Qur’an, which focus on the development of a very clear concept of moderate religiosity without any obscurity and confusion. Moderation is one of the favors of Allah which He bestowed upon the Muslims and honored them as He made them the best, just, moderate nation as mentioned in the Qur’an. But after many graceful centuries, dispersions and differences appeared as many sects emerged with innovations, exaggerations, and tempting incitements. The emergence of innovations continued and hence generations of people inherited a lot of cardinal and practical deviations and thus moved away from the moderate approach as charted by the Qur’an. The researchers used descriptive method to study the Qur’anic approach regarding religiosity by explaining the meaning of the moderation in the Qur’an regarding the faith in Allah, His angels, His books, His Messengers, the Last Day, and fate and destiny . In addition to that the researchers mentioned some examples of deviant religiosity as recorded in the Qur’an whether it is because of exaggeration or excessiveness so as to be clear about moderate religiosity